PEDAGOGICAL CONDITIONS OF DEVELOPMENT OF THINKING ABILITY OF PRIMARY CLASS STUDENTS BASED ON PROBLEM EDUCATION METHOD - Kholmurotova, Aziza (Журнал иностранных языков и лингвистики, 2022)
The article covers the information about the formation of the ability to draw conclusions by developing the thinking ability of primary school students based on the method of problem-based education.